Experiences of support for people who access voluntary, community and social enterprise (VCSE) organisations for self-harm: a qualitative study with stakeholder feedback - Joe Hulin; Vyv Huddy; Phillip Oliver; Jack Marshall; Aarti Mohindra; Brigitte Delaney; Caroline Mitchell (BMC, 2024)
Abstract Background Prevalence of self-harm In England is rising, however contact with statutory services remains relatively low. There is growing recognition of the potential role voluntary, community and social enterprise sector (VCSE) organisations have in the provision of self-harm support. We aimed to explore individuals' experiences of using these services and the barriers and facilitators to accessing support. Methods Qualitative, online interviews with 23 adults (18+) who have accessed support from VCSE organisations for self-harm in the Yorkshire and the Humber region were undertaken. Interviews were audio recorded and transcribed verbatim. Thematic analysis was undertaken using NVivo software. Results Participants described how a lack of service flexibility and the perception that their individual needs were not being heard often made them less likely to engage with both statutory and VCSE organisations. The complexity of care pathways made it difficult for them to access appropriate support when required, as did a lack of awareness of the types of support available. Participants described how engagement was improved by services that fostered a sense of community. The delivery of peer support played a key role in creating this sense of belonging. Education and workplace settings were also viewed as key sources of support for individuals, with a lack of mental health literacy acting as a barrier to access in these environments. Conclusions VCSE organisations can play a crucial role in the provision of support for self-harm, however, pathways into these services remain complex and links between statutory and non-statutory services need to be strengthened. The provision of peer support is viewed as a crucial component of effective support in VCSE organisations. Further supervision and training should be offered to those providing peer support to ensure that their own mental health is protected.